1996
DOI: 10.1111/j.1749-6632.1996.tb39080.x
|View full text |Cite
|
Sign up to set email alerts
|

Senescence‐Accelerated Mouse

Abstract: Senescence-accelerated mouse (SAMP8) is known as a murine model of accelerated aging and memory dysfunction. The binding activity of [3H] 1-(2-chlorophenyl)-N-methyl-N-(1-methylpropyl)-3-isoquinolinecarboxam ide (PK-11195) as a neurochemical marker of gliosis markedly increased with aging in the cerebral cortex and hippocampus of SAMP8. Immunoreactivity for glial fibrillary acidic protein (GFAP) was also enhanced. A beta-amyloid precursor protein (APP)-like immunoreactivity and 27-kDa-carboxyl terminal fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Morley et al (2000) found Aβ plaques that were not discernible before 16 months of age and became more prevalent at 22 months of age. However, Nomura et al (1996) found no evidence of deposits or granular structures in SAMP8 brain although they reported an increase in APP-like immunoreactivity. From their description, the Aβ-LI and reelin deposits containing Aβ reported by Knuesel et al (2009) would appear to be the pathological granules that we have investigated further in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Morley et al (2000) found Aβ plaques that were not discernible before 16 months of age and became more prevalent at 22 months of age. However, Nomura et al (1996) found no evidence of deposits or granular structures in SAMP8 brain although they reported an increase in APP-like immunoreactivity. From their description, the Aβ-LI and reelin deposits containing Aβ reported by Knuesel et al (2009) would appear to be the pathological granules that we have investigated further in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Learning and memory in the SAMP8 strain has been assessed using several paradigms, including watermaze, T-maze, passive avoidance, and one-way active avoidance tests, with declines in cognitive function evident at 2 months of age, and significantly at 4 months as compared with normal aging SAMR1 mice [16]. In an immunoblot analysis, we found that amyloid precursor protein (APP)-like protein was increased with age in the brain of SAMP8, associated with an increase in gliosis and glial fibrillary acidic protein (GFAP) [9]. Recently, Takemura et al [17] found that b/A4 protein-like immunoreactive granular structures (b-LIGS) increased with age using a polyclonal antibody to b/A4 protein fragments 10-42 in SAMP8 and SAMR1.…”
Section: Introductionmentioning
confidence: 92%
“…Previous studies by ourselves and others revealed reduction in the amounts of neurotransmitters released from brain slices [2,3], decreases in levels of muscarinic acetylcholine, and serotonine-1A and NMDA receptors [4,5], and decreases in protein kinase C [5,6] and synaptic spine density [7]. Genes related to Alzheimer's disease (AD) were found in the SAMP8 brain [8], and b-amyloid (Ab) deposits were found in the brains of aged SAMP8 mice [9,10]. Abnormal granular structures, which stained positively with periodic acid-Schiff (PASpositive granular structures; PGS), have also been observed in the SAMP8 brain [11].…”
Section: Introductionmentioning
confidence: 99%
“…In-vitro study using human platelet cells showed a non-significant difference in TSPO density between young and older subjects (Marazziti et al, 1994). However, a radioligand binding assay study using the classical TSPO radioligand [ 3 H]-PK11195 in an animal model of aging showed an age-related increase in TSPO binding in the cerebral cortex and hippocampus (Nomura et al, 1996). …”
Section: Introductionmentioning
confidence: 99%